STRUKTUR ORGANISASI SEKOLAH DAN IMPLIKASINYA TERHADAP EFEKTIVITAS PENGAMBILAN KEPUTUSAN MANAJERIAL - M. Hasan Basari; Manarur Mizal; Zaid Halim Nur Rahmat; Muhammad Kholil Alghoffaar (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study examines the relationship between school organizational structure and the effectiveness of managerial decision-making. An appropriate organizational structure is a crucial foundation for determining how decisions are made, communicated, and implemented in an educational context. Through an analysis of various structural models, this study found that structural flexibility, hierarchical clarity, and coordination mechanisms significantly influence the speed and quality of decision-making in schools.